HydroFlipper membrane tension probes: imaging membrane hydration and mechanical compression simultaneously in living cells. Issue 7 (3rd February 2022) - García-Calvo, José; López-Andarias, Javier; Maillard, Jimmy; Mercier, Vincent; Roffay, Chloé; Roux, Aurélien; Fürstenberg, Alexandre; Sakai, Naomi; Matile, Stefan
Abstract : HydroFlippers respond to membrane compression and hydration in the same fluorescence lifetime imaging microscopy histogram: the responses do not correlate. Abstract : HydroFlippers are introduced as the first fluorescent membrane tension probes that report simultaneously on membrane compression and hydration. The probe design is centered around a sensing cycle that couples the mechanical planarization of twisted push–pull fluorophores with the dynamic covalent hydration of their exocyclic acceptor. In FLIM images of living cells, tension-induced deplanarization is reported as a decrease in fluorescence lifetime of the dehydrated mechanophore. Membrane hydration is reported as the ratio of the photon counts associated to the hydrated and dehydrated mechanophores in reconvoluted lifetime frequency histograms. Trends for tension-induced decompression and hydration of cellular membranes of interest (MOIs) covering plasma membrane, lysosomes, mitochondria, ER, and Golgi are found not to be the same. Tension-induced changes in mechanical compression are rather independent of the nature of the MOI, while the responsiveness to changes in hydration are highly dependent on the intrinsic order of the MOI. These results confirm the mechanical planarization of push–pull probes in the ground state as most robust mechanism to routinely image membrane tension in living cells, while the availability of simultaneous information on membrane hydration will open new perspectives in mechanobiology.